Demographic and clinical characteristics of primary glomerular diseases in Turkey - KOÇ, MEHMET (SPRINGER, 2014)
The aim of our study was to delineate the demographic and clinical properties of primary glomerular diseases of adult population in our country in the light of global knowledge. All over the country, a total of 25 centers entered data between May 2009 and July 2012 to the database created by 'Glomerulonephritis Study Group' of Turkish Society of Nephrology. Demographic and clinical characteristics, specific diagnoses of glomerular diseases and biopsy findings recorded to the database were analyzed. Among the 1,274 patients, who had renal biopsy within the defined time period, 55 % were male and 45 % were female. The mean age was 40.8 +/- A 14.6 years. The most frequent indication for biopsy was nephrotic syndrome (57.8 %), followed by nephritic syndrome including rapidly progressive glomerulonephritis (16.6 %) and asymptomatic urinary abnormalities (10.8 %). The most frequent primary glomerular disease was membranous nephropathy (28.8 %), followed by focal segmental glomerulosclerosis (19.3 %) and IgA nephropathy (17.2 %). The presented study displayed important data about the epidemiology of primary glomerular diseases among adults in our country. The predominance of membranous nephropathy in contrast to other countries, in which the most frequent etiology is IgA nephropathy, seems to be due to differences in the indications for renal biopsy.
Keywords: Glomerulonephritis; Primary glomerulonephritis; Primary glomerular diseases; Turkish Society of Nephrology; Turkey; CHRONIC KIDNEY-DISEASE; RENAL-DISEASES; EPIDEMIOLOGIC DATA; NEPHROTIC SYNDROME; IGA NEPHROPATHY; REGISTRY; GLOMERULONEPHRITIS; MORTALITY; BIOPSIES; ADULTS